Serosurvey of Avian Influenza Viruses (H5, H7, and H9) and Associated Risk Factors in Backyard Poultry Flocks of Lahore District, Pakistan - Chaudhry, Mamoona; Rashid, Hamad Bin; Thrusfield, Michael; Eisler, Mark C.; Welburn, Susan C. (Frontiers in Veterinary Science, 2021)
Rural poultry constitutes 56% of the total poultry population in Pakistan; however, epidemiological information about avian influenza viruses (AIVs) in backyard poultry flocks is lacking. A cross-sectional survey of villages of Lahore district was conducted from July 2009 to August 2009 using two-stage cluster sampling and probability proportional to size (PPS) sampling to estimate seroprevalence and its associated risk factors. A random selection of 35 clusters from 308 villages of Lahore were considered, and from each cluster, six chickens aged >2 months were selected. A total of 210 serum samples were collected and examined by the hemagglutination inhibition (HI) test for specific antibodies against AIV subtypes H5, H7, and H9. Overall weighted seroprevalence for AIVs was 65.2% (95% CI: 55.6–74.8%), and for subtype H5, H7 & H9 was 6.9% (95% CI: 10.8–23.0%), 0% (95% CI: 0–1.7%), and 62.0% (95% CI: 52.2–71.8%) respectively. However, none of the samples were positive for H7. The average flock size was 17.3 birds, and the main purpose of keeping poultry was for eggs/meat (70.6%, 95% CI: 59.7–81.4). A majority of them were reared in a semi-caged system (83%, 95% CI: 74.5–91.3). Backyard birds were received from different sources, that is, purchased from the market or received as a gift from friends or any NGO, and were 5.7 times more likely to become avian influenza (AI) seropositive than those that were not exposed to these sources (CI 95%: 2.0–716.0). Backyard birds which were received from different sources, that is, purchased from the market or received from friends or any NGO, were 5.7 times more likely to become AI seropositive compared to those that were not (CI 95%: 2.5–18.7). To reduce the risk of AIV in Pakistan, continuous surveillance of backyard poultry would be needed.